1995
DOI: 10.1183/09031936.95.08101770
|View full text |Cite
|
Sign up to set email alerts
|

Models and mechanisms of exercise-induced asthma

Abstract: M Mo od de el ls s a an nd d m me ec ch ha an ni is sm ms s o of f e ex xe er rc ci is se e--i in nd du uc ce ed d a as st th hm ma a A.N. FreedModels and mechanisms of exercise-induced asthma. A.N. Freed. ERS Journals Ltd 1995. ABSTRACT: Airflow-induced bronchoconstriction (AIB) in mammals can be broadly categorized as either vagal-dependent or vagal-independent. Among mammals, rabbits and cats belong to the former and guinea-pigs belong to the latter categories. Although insufficient data are available t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 99 publications
0
52
0
1
Order By: Relevance
“…Previous studies have demonstrated hyperosmolar insults may result in increased airway responsiveness in rabbits (25) and increased vascular permeability (and possibly neuropeptide release) in rats (26). In addition, intracellular fluid loss in lung epithelial cells (as could occur after instillation of the rats with a hyperosmolar salt solution) is thought to contribute to exercise-induced bronchoconstriction, late-phase asthmatic responses (27), and increased chemokine expression in airway epithelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated hyperosmolar insults may result in increased airway responsiveness in rabbits (25) and increased vascular permeability (and possibly neuropeptide release) in rats (26). In addition, intracellular fluid loss in lung epithelial cells (as could occur after instillation of the rats with a hyperosmolar salt solution) is thought to contribute to exercise-induced bronchoconstriction, late-phase asthmatic responses (27), and increased chemokine expression in airway epithelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…The urinary excretion (mean±SE) of 9α,11β-PGF 2 Eur Respir J 1998;12: 345-350. and N τ -methylhistamine, was measured before and after exercise challenge in a group of asthmatics with a history of EIB. The major cyclooxygenase product of mast cells PGD 2 , is metabolized in the lung, via the action of the reduced nicotinamide adeine dinucleotide phosphate (NADPH)-dependent enzyme 11-ketoreductase to 9α, 11β-PGF 2 , and is excreted intact into the urine [24].…”
Section: Aamentioning
confidence: 99%
“…It is characterized by transient airflow obstruction resulting in a Š15% decrease in forced expiratory volume in one second (FEV1) following 5-8 min of exercise. The fall in FEV1 reaches a maximum approximately 10 min after exercise and gradually normalizes over the next hour [2]. The precise pathophysiology of EIB remains unclear, although it is widely accepted that during exercise the upper airways are unable to adequately warm and humidify the increased volumes of inspired air.…”
mentioning
confidence: 99%
“…23 It causes transient dehydration of the bronchial mucosa due to the low water content of the air, leading to a hyperosmolarity of the mucosal fluid of the airway surface lining, which may damage bronchial epithelial cells. 1,14 The hyperosmolarity of the mucosal fluid alters the osmotic gradient throughout the mucosa and sub-mucosa, resulting in the activation and degranulation of mast cells in the sub-mucosa. Degranulation of these mast cells results in the release of pro-inflammatory mediators and the activation of cholinergic receptors.…”
Section: Dry Cold Airmentioning
confidence: 99%